Scoring Algorithms for Predicting Survival Prognosis in Patients With Metastatic Spinal Disease: The Current Status and Future Directions. Issue 8 (October 2020) - Cui, Yunpeng; Lei, Mingxing; Pan, Yuanxing; Lin, Yunfei; Shi, Xuedong
Abstract : Various survival scoring systems have been developed to help surgeons select the best candidates for appropriate therapies in patients with metastatic spinal disease. This study aims to discuss the current status and future directions of scoring systems for the prediction of survival prognosis in these patients. The search terms "spine metastases, " "metastatic spinal disease, " and "metastatic spinal cord compression" were combined with "survival prognosis, " "scoring system, " and "score" to elicit relevant literatures in PubMed and Embase databases. As a result, 159 articles were selected from PubMed, and 246 articles were extracted from Embase. After reviewing each article, we carefully included and analyzed 74 articles about the development and evaluation of scoring systems for predicting survival prognosis in spine metastases. In this review, those scoring systems were stratified into the historic scoring systems and the modern scoring systems on the basis of the proposed time. The historic scoring systems, including the original/revised Tokuhashi scoring system, the Bauer scoring system, the Tomita scoring system, and the Linden scoring system, and the modern scoring systems, such as the Lei scoring system, the Bartels scoring system, the Mizumoto scoring system, the Bollen scoring system, the Rades scoring system, Oswestry Spinal Risk Index, and the Choi risk calculator, were introduced and discussed in this review. Besides, the clinical effectiveness and pitfalls of the existing systems and the future directions of the next generation of scoring systems were also addressed and discussed. We recommended these scoring systems as preferable reference tools to help doctors to select surgical candidates. In patients with long-term life expectancy, radical surgery, such as wide or marginal excision, can be considered in patients with neurological deficits, spine instability, or severe back pain. Besides, with the advancement and improvement of medical technologies, surgical procedures are changing, which can affect surgical indications such as vertebroplasty, minimal invasive surgery, and percutaneous stabilization, which can also be used in patients with spine instability or severe back pain, and do not require much recovery; hence, they can even be used in patients with relative short-term life expectancy. However, the decision about the treatment of patients with metastatic spinal disease is so complicated and should never rely on prognostic scores alone. The final therapeutic decision should be made by interdisciplinary corporations of oncologists, radiologists, and spinal surgeons. Besides, individual intentions should be respected.